Peningkatan Motivasi Siswa dalam Menyelesaikan Tugas Melalui Layanan Informasi - Hezy Desyafmi; Firman Firman; Ifdil Ifdil (Universitas Negeri Padang, 2016)
Motivation is very important for students as teenagers in order to actualate their achievement. Finishing their task is one way for the students to comprehend the lesson. Motivation is definitely needed by the students to finish their task at school. In fact, the students stiil have low motivation in studying. Guidance and counselling teacher is one part that try to improve students' motivation in finishing their task. This research aims to describe the condition of students' motivation in finishing their task before and after giving information service also indentify the degree of difference. The research used qualitative method with quasi experiment technique and one group pretest and posttest design. The subject is VII grade students of MTsN Sei. Jambu for 20 students. The instruments is motivation. Data analysis percentage and axamine also the degree of difference by using wilcoxon signed ranks test technique using SPSS version 20.0. finding shows that the students' motivation in pretest is middle category with average score 161,9 and posttest is also in middle category with 179,3 average score. It shows that there is significant difference of students' motivation in finishing their task before and after giving information service. Based on this result, it is suggested to guidance and counselling teacher to keep improve giving information service to the students in order to motivate students in finishing their task.